Early production of evidence in benefits maintained under Social Security (Revista do Tribunal Regional Federal da 3ª Região, 2018)
The purpose of this article is to verify the scope of the request for early production of evidence aimed at granting benefits under the social security system. The study will begin with some reflections on the institute in the current legal system in comparison with the old procedural law. Mention will also be made of some specific issues relating to incapacity benefits in the social security sphere. Next, the administrative request will be examined, which characterizes the interest in acting in the benefit requests in question. This is an issue of fundamental importance, especially with regard to applications for disability benefits. Finally, a very important aspect of this work will deal with the question of whether or not the request for advance production of evidence, in social security and welfare matters, must be preceded by a prior administrative request.
Keywords: early production of evidence; social security; evidence; prior administrative request